Diet composition and food overlap of Acestrorhynchus britskii and A. lacustris (Characiformes: Acestrorhynchidae) from Sobradinho reservoir, São Francisco river, Bahia State - doi: 10.4025/actascibiolsci.v33i4.7240 - Rocha, Aline Alves Ferreira da (2011)
Fish diet studies contribute to understanding resource partitioning and community trophic structure. The present paper characterizes the diet of “peixe-cachorro” species Acestrorhynchus britskii and A. lacustris in Sobradinho reservoir, Bahia State, Brazil. Bimonthly samples (November 2006 to July 2008) were taken in the lotic, transition and lentic stretches of the reservoir, using gillnets overnight. A total of 899 A. britskii and 476 A. lacustris stomachs were analyzed, 70% of which were empty. Their content indicated the species are predominantly piscivorous, with 18 prey fish species identified. However, each prey occurred in a single month, except for Anchoviella vaillanti, recorded in 80% of months for A. bristski, and Tetragonopterus chalceus in 25% for A. lacustris. The species presented high food overlap (Cλ = 0.992), owing to the occurrence of Actinopterygii (bits) and Actinopterygii in all months. Regarding prey fish alone, a differentiated intake and lower food overlap was detected, in the flood (Cλ = 0.427) and drought (Cλ = 0.172) seasons, in the lotic (Cλ = 0.434), transition (Cλ = 0.089) and lentic (Cλ = 0) stretches, and in overall overlap (Cλ = 0.236). The spatial and seasonal differences in the intake of different prey fish by both species suggest an opportunistic feeding habit and a competition reduction mechanism for food resources.